2004
DOI: 10.1093/protein/gzh062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of leucine-rich nuclear export signals

Abstract: We present a thorough analysis of nuclear export signals and a prediction server, which we have made publicly available. The machine learning prediction method is a significant improvement over the generally used consensus patterns. Nuclear export signals (NESs) are extremely important regulators of the subcellular location of proteins. This regulation has an impact on transcription and other nuclear processes, which are fundamental to the viability of the cell. NESs are studied in relation to cancer, the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
636
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 706 publications
(665 citation statements)
references
References 72 publications
25
636
1
3
Order By: Relevance
“…This indicated the presence of one or several LMB-sensitive NES in GFP-Pyk2 700-841 . The L 730 LAPKLQFQVP sequence of Pyk2A was identified as putative NES by the NetNES 1.1 server [41]. We mutated the 3 hydrophobic residues (L735A/F737A/V739A, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated the presence of one or several LMB-sensitive NES in GFP-Pyk2 700-841 . The L 730 LAPKLQFQVP sequence of Pyk2A was identified as putative NES by the NetNES 1.1 server [41]. We mutated the 3 hydrophobic residues (L735A/F737A/V739A, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The RASSF1A/p120 E4F association was found to enhance G1 cell-cycle arrest and S-phase inhibition and promote the stabilization of cyclins (Fajas et al, 2001;Fenton et al, 2004). Within the primary sequence of RASSF1A, two potential nuclear export sequences can be found that follow the consensus sequence, LxxxLxxL (la Cour et al, 2004): 10 LIELREL and 301 LHNFLRIL (numbers denote amino-acid number within the primary sequence of human RASSF1A). It is interesting that 17/35 (48%) of the leucine residues within the primary sequence are found within the last 100 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Fluc-EGFP and FlucDM-EGFP were tagged with either a nuclear export signal (NES) (shown in yellow) or a nuclear localization signal (NLS) (shown in red) at the N-terminus to study proteostasis of the cytoplasm and the nucleus respectively. whereas, NES was derived from a consensus sequence obtained from prediction algorithm program (The NES predictor, NetNES) (http://www.cbs.dtu.dk/services/NetNES/) using experimentally validated sequences rich in leucine residues (la Cour et al, 2004).…”
Section: Egfp Variantsmentioning
confidence: 99%